Strategi Penanaman Kebiasaan Beribadah Pada Anak (Studi Kasus Pada Masyarakat Muslim Minoritas Desa Kuta Gugung Kabupaten Karo) - Muhammad Yunan Harahap; Masruroh Lubis; Muhammad Ali Hanafiah (Intiqad: Jurnal Agama dan Pendidikan Islam, 2019)
Cultivating worship habits in children in a minority environment is certainly not easy. Because minority conditions are correlated with a minimal amount of worship activity, the outcome is certainly on the impact of the reduced motivation to worship in children. This study aims to (1) determine the strategies carried out by parents in instilling worship habits in children, in the Desa Kuta Gugung Kec. Namanteran Kab. Karo, (2) Knowing the factors that influence the difficulty of instilling worship habits in children in the Desa Kuta Gugung Kec. Namanteran Kab. Karo. The method used in this research is the qualitative method, with a case study approach. The results of this study indicate that the strategies used in inculcating worship habits to children are (1) exemplary, (2) Magrib Mengaji Program, (3) attending joint study, (4) practicing it with the activity sunnah, (4) instilling religious traditions. While the factors of difficulty in instilling worship habits in children are (1) the number of minority Muslims, (2) the lack of religious knowledge, (3) the eruption of Gugung Sinabung disaster.